Intake of Soy, Soy Isoflavones and Soy Protein and Risk of Cancer Incidence and Mortality - Fan, Yahui; Wang, Mingxu; Li, Zhaofang; Jiang, Hong; Shi, Jia; Shi, Xin; Liu, Sijiao; Zhao, Jinping; Kong, Liyun; Zhang, Wei; Ma, Le (Frontiers in Nutrition, 2022)
Background and aims: Associations between soy intake and risk of cancer have been evaluated in prospective observational studies with inconsistent results. Whether the potential anticancer effects offered by soy were attributed to soy isoflavones and soy protein still needs to be elucidated. This study aimed to comprehensively quantify the association of soy, soy isoflavones and soy protein intake with risk of cancer incidence and cancer mortality by conducting a meta-analysis of all available studies. Methods: PubMed, Embase, Web of Science, and Cochrane Library databases were searched up to 16 September 2021. Prospective cohort studies that examined the effect of soy, soy isoflavones and soy protein on cancer incidence and cancer mortality were identified. Random-effects models were used to pool the multivariable-adjusted relative risks (RRs) and corresponding 95% confidence intervals (CIs). The potential dose-response relations were explored by using generalized least-squares trend estimation. Results: 81 prospective cohort studies were included in the meta-analysis. A higher intake of soy was significantly associated with a 10% reduced risk of cancer incidence (RR, 0.90; 95% CI, 0.83-0.96). Each additional 25 g/d soy intake decreased the risk of cancer incidence by 4%. Intake of soy isoflavones was inversely associated with risk of cancer incidence (RR, 0.94; 95% CI, 0.89-0.99), whereas no significant association was observed for soy protein. The risk of cancer incidence was reduced by 4% with each 10 mg/d increment of soy isoflavones intake. Similar inverse associations were also found for soy in relation to site-specific cancers, particularly lung cancer (RR, 0.67; 95%CI, 0.52-0.86) and prostate cancer (RR, 0.88; 95%CI, 0.78-0.99). However, high intake of soy, soy isoflavones and soy protein were not associated with cancer mortality. Conclusions: Higher intake of soy and soy isoflavones were inversely associated with risk of cancer incidence, which suggested that the beneficial role of soy against cancer might be primarily attributed to soy isoflavones. These findings support recommendations to include soy as part of a healthy dietary pattern for the prevention of cancer.